Peran Pendidikan Dalam Membangun Kemanusiaan Yang Beradab - Muthi’ah Lathifah; Yakobus Ndona (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This study aims to understand the role of education in fostering a civilized humanity. The research method used is a descriptive qualitative method with a literature review approach. Education plays a crucial role in building a civilized humanity. The main goal of education is not only to transfer knowledge but also to develop character, moral values, and ethics that support harmonious coexistence. In this context, education functions as an agent of social change that can shape individuals who are responsible, tolerant, and respectful of differences. This article analyzes how education can contribute to building a civilized society by reinforcing human values such as justice, equality, and mutual respect. The analysis results show that effective and inclusive education can serve as the main foundation in efforts to build a civilized and sustainable humanity.